KLB Keracunan Makanan Di Dusun Kacepit, Desa Wulungsari, Kecamatan Selomerto, Kabupaten Wonosobo, 2024 - Gosari, Kevin Rayes; Adi, Mateus Sakundarno; Martini, Martini; Misinem, Misinem (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: A food poisoning incident occurred on Saturday, February 24, 2024, during a religious gathering in Kecapit Hamlet, Wulungsari Village, Selomerto Sub-district, with a total of 44 cases. The objective of this investigation was to identify the source of the outbreak and the risk factors associated with the food poisoning incident.Methods: Food poisoning was defined as a condition in individuals experiencing illness with symptoms and signs of poisoning caused by consuming food suspected of containing biological or chemical contaminants. An outbreak investigation using a cross-sectional study design was conducted. Research questionnaires were used to collect data on risk factors as well as signs and symptoms. A total of 58 individuals who attended the event were included as samples. These factors were analyzed descriptively, and attack rates were calculated for each factor. Fecal samples from clinically ill cases were collected for laboratory testing.Results and Discussion: Out of the 58 individuals, 44 experienced symptoms of diarrhea >3 times (72.4%), abdominal cramps (69%), fever (62.1%), vomiting (22.4%), and nausea (58.4%). More cases were detected in males (52%) with an age range of 5-81 years (average 41.7 years). The incubation period ranged from 6-15 hours (average 11.41 hours). The investigation results indicated that individuals who consumed durian coconut syrup became ill (44/58; Attack Rate 93.6%). Stool laboratory test results showed positive for Salmonella. However, laboratory testing for the durian coconut syrup was not conducted in this study due to the unavailability of samples.Conclusion: Based on the findings of the investigation, it can be concluded that the cause of the food poisoning was durian coconut syrup contaminated with Salmonella bacteria. This contamination may have occurred because the food spoiled as it was prepared at 8:00 AM and served in the afternoon (3:00 PM).